Analisis Maqasid Al-Shariah Terhadap Peran Pemerintah Kota Surabaya dalam Mewujudkan Kota Layak Anak - Zakiyatul Ulya (AL-HUKAMA, 2020)
The research entitled: "Maqasid al-Shari'ah Analysis of the Role of the Surabaya City Government in Realizing Child Friendly Cities" is a field research that aims to answer the question how the role of the Surabaya City Government in realizing Child Friendly Cities through established public policies from the perspective of the maq??id al-shar?'ah. Research data were collected using interview and documentation techniques and then analyzed using descriptive analysis techniques with a deductive mindset. The results of the study concluded that the Surabaya City Government was very active in realizing Child Friendly Cities through the protection and fulfillment of children's rights, which was clearly seen from the existence of various public policies that were established to support institutional strengthening and fulfillment of the five Child Friendly Cities clusters.The role of the Surabaya City Government is in accordance with the concept of maqasid al-shari'ah because the determination of public policy is based on the welfare of children. This is proven by the elements of hifz al-din and hifz al-nasl in the public policy regarding civil rights and freedom, family environment, and alternative protection. In addition, there are elements of hifz al-nafs and hifz al-aql in public policies regarding institutional strengthening and the five Child Friendly Cities clusters, although they are actually less than perfect due to the absence of the hifz al-mal elements in them.